Balloon dilation atrial septostomy for advanced pulmonary hypertension in patients on prostanoid therapy. Issue 6 (10th December 2014) - Kuhn, Brooks T.; Javed, Usman; Armstrong, Ehrin J.; Singh, Gagan D.; Smith, Thomas W.; Whitcomb, Charles J.; Allen, Roblee P.; Rogers, Jason H.
<x xml:space="preserve">Abstract</x> Background : Prostanoid therapy improves quality of life and may increase survival in patients with advanced pulmonary hypertension (PH). Balloon dilated atrial septostomy (BDAS) can palliate or bridge to transplantation for patients resistant to medical therapy. The safety and efficacy of BDAS in the prostanoid era has not previously been reported. Methods: All patients had progressive symptoms despite prostanoid therapy at the time of their first BDAS. Sixteen patients who underwent a total of 23 septostomies between 2004 and 2014 were included in this retrospective case series. Results: Patients were aged 47.6 years ± 11.3 with 12/16 women. Etiologies included idiopathic (7), methamphetamine (6), scleroderma (1), and anorexigen (2). One patient died within 24 hr post‐procedure. Thirty‐day and 1‐year survival were 75% and 64%, respectively. Six of the septostomies were revisions, including two which were ultimately stented. Three subjects were successfully bridged to transplant. Pulmonary capillary wedge pressure (PCWP) increased from a mean of 13 to 17 mm Hg, cardiac index increased from 2.1 to 2.4 L/min/m2, and arterial saturation decreased from 90.7 ± 4.3 to 82.5 ± 5.6%. All non‐survivors at 30 days were male and had higher baseline serum creatinine, mean RAP, right ventricular end diastolic pressure (RVEDP), and left ventricle (LV) filling pressures, and lower right ventricle (RV) ejection fraction. Mortality was associated with unchanged post‐septostomy cardiac output despite an increase in left ventricular end diastolic pressure (LVEDP). Conclusions: BDAS may be an alternate therapy for select PH patients who have symptomatic progression despite prostanoid therapy. Survival is comparable to prior reports of BDAS in the pre‐prostanoid era. © 2014 Wiley Periodicals, Inc.